1998
DOI: 10.1111/j.1540-8159.1998.tb00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Syncope: Loss of Consciousness Associated with Cerebral Vasoconstriction in the Absence of Systemic Hypotension

Abstract: Transcranial Doppler (TCD) ultrasonography done during head-upright tilt induced neurocardiogenic syncope has demonstrated that cerebral vasoconstriction occurs concomitant with (or precedes) loss of consciousness. This article demonstrates evidence that cerebral blood flow changes alone (vasoconstriction), in the absence of systemic hypotension, may result in syncope. Five patients (4 men, 1 woman; mean age 41 +/- 17 years) with recurrent unexplained syncope were evaluated by use of an upright tilt table test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 21 publications
2
50
0
1
Order By: Relevance
“…The nondrug-using individuals in our sample fell within the normative range for both blood flow velocity and PI, thus supporting the absence of measurement error. Slowed cerebral blood flow velocity with increased pulsatility in certain patient populations indicate increased cerebrovascular resistance was due to vasoconstriction of small cortical vessels (Martin et al 1994;Biedert et al 1995;Cho et al 1997;Schondorf et al 1977;Grubb et al 1998). Such an interpretation of pulsatility does not hold in situations where blood pressure differed among groups (Czosnyka et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…The nondrug-using individuals in our sample fell within the normative range for both blood flow velocity and PI, thus supporting the absence of measurement error. Slowed cerebral blood flow velocity with increased pulsatility in certain patient populations indicate increased cerebrovascular resistance was due to vasoconstriction of small cortical vessels (Martin et al 1994;Biedert et al 1995;Cho et al 1997;Schondorf et al 1977;Grubb et al 1998). Such an interpretation of pulsatility does not hold in situations where blood pressure differed among groups (Czosnyka et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…Altered cerebrovascular control unrelated to changes in PET CO 2 has been reported during LBNP following bed rest (44) and parabolic flight (38). In addition, a paradoxical cerebral vasoconstriction in healthy (5,6,22,38) and orthostatically intolerant (13,14) individuals has been reported during postural stress and LBNP. However, our previous work (38), as well as that of others (8,21), showed that cerebral autoregulation remains intact during HUT in healthy subjects, suggesting that decreases in perfusion pressure were unlikely to be the cause of the decrease in cerebral flow.…”
Section: Discussionmentioning
confidence: 94%
“…The central role of the thalamus in the regulation of consciousness is further supported by the widespread thalamic neuronal cell death observed in vegetative state patients [111]. Another example, which illustrates the central role of the thalamo-cortical system as a core component of the neuronal substrate of consciousness, is that vasoconstriction of the middle cerebral artery, which provides blood to both cerebral cortex and the thalamus, can result in a transient loss of consciousness (syncope), associated with an increase of slow wave activity in the EEG indicative of functional inactivation of the cortex [112]. Also, TCD is accompanied by a characteristic downward shift of the power spectrum [108].…”
Section: (A) the Neuronal Substrate Of Consciousnessmentioning
confidence: 99%